Fundamentals of general, organic, and biological chemistry (Pearson, 2018)
Matter and life -- Measurements in chemistry -- Atoms and the periodic table -- Ionic compounds -- Molecular compounds -- Chemical reactions: classification and mass relationships -- Chemical reactions: energy, rates, and equilibrium -- Gases, liquids, and solids -- Solutions -- Acids and bases -- Nuclear chemistry -- Introduction to organic chemistry: alkanes -- Alkenes, alkynes, and aromatic compounds -- Some compounds with oxygen, sulfur, or a halogen -- Amines -- Aldehydes and ketones -- Carboxylic acids and their derivatives -- Amino acids and proteins -- Enzymes and vitamins -- Chemical messengers: hormones, neurotransmitters, and drugs -- The generation of biochemical energy -- Carbohydrates -- Carbohydrate metabolism -- Lipids -- Lipid metabolism -- Nucleic acids and protein synthesis -- Genomics -- Protein and amino acid metabolism -- Body fluids. ;Includes index.